2013
DOI: 10.1002/bab.1095
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ammonium salts on the lipase/esterase activity assay using p‐nitrophenyl esters as substrates

Abstract: p-Nitrophenyl esters with a short-chain carboxylic group, such as p-nitrophenyl acetate (p-NPA) and p-nitrophenyl butyrate (p-NPB), could be effectively hydrolyzed by ammonium salts. p-Nitrophenyl esters were usually used as substrates to assay the lipase/esterase activity. Ammonium sulfate precipitation was often used to purify proteins, and some ammonium salts were usually used as nitrogen sources or inorganic salts for the lipase/esterase production. To study the effect of ammonium salts on the assay of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Subsequently, it was observed that ammonium ions could trigger the hydrolysis of the substrate used in the assay, leading to false-positive results. The same observation was published for different p NP-esters . Further, it was observed that when ammonium sulphate was removed by dialysis, the volumetric activity of the supernatant was reduced to the initial value.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Subsequently, it was observed that ammonium ions could trigger the hydrolysis of the substrate used in the assay, leading to false-positive results. The same observation was published for different p NP-esters . Further, it was observed that when ammonium sulphate was removed by dialysis, the volumetric activity of the supernatant was reduced to the initial value.…”
Section: Resultssupporting
confidence: 79%
“…The same observation was published for different pNP-esters. 29 Further, it was observed that when ammonium sulphate was removed by dialysis, the volumetric activity of the supernatant was reduced to the initial value. The obtained results indicate that lipase has not been precipitated at these conditions (70% ammonium sulphate, T = 4 °C, t = 5 h, pH 8, 1.89 mg cm −3 proteins).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Esterase and lipase activities were quantified by following the hydrolysis of p-nitrophenyl esters and measured spectrophotometrically at 415 nm (De Yan et al, 2013). Substrate p-NPB for esterase activity and substrate 4-p-NPC for lipase activity were prepared as follows.…”
Section: Lipolytic Activity Quantificationmentioning
confidence: 99%
“…Esterase activity was determined spectrophotometrically using 4-nitrophenyl butyrate as a specific esterase substrate hydrolyzed to a colored product 4nitrophenolate ion with an optical absorbance λ max = 400 nm. 31 The assay was performed at different bulk pH values to analyze the esterase activity dependence on the pH. The used pH values were based on the known dependence of the esterase activity on solution pH.…”
Section: Methodsmentioning
confidence: 99%